COMPANY CHARACTERISTICS INFLUENCE AUDIT REPORT LAG: MODERATING ROLE AUDITOR’S REPUTATION - Kaafah, Najwa Silmi; Mardi; Handarini, Dwi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to measure the influence of company size and financial report complexity on audit report lag, with the auditor's reputation variable as a moderator variable. This research is classified as quantitative. The population of the research consists of real estate and property firms that are listed on the Indonesia Stock Exchange in 2023. The data analysis technique uses multiple regression analysis and Moderated Regression Analysis (MRA), to test whether or not there is a role for moderating variables. This research shows that a company's size has a significant and adverse effect on how long it takes to provide audit reports. Furthermore, there is a noteworthy and positive correlation between the intricacy of financial reports and the latency of audit reports. Nonetheless, the impact of financial report complexity and firm size on audit report delay is unaffected by the auditors' reputation.